MULTI-CRITERIA DECISION MAKING FOR BUSINESS VALUE CREATION - Solana-González, Pedro (2021)
Multi-criteria decision making for business value creation has become a topic of significant interest that, however, has not yet been sufficiently studied. Companies find it difficult to determine the best decision criteria for creating value. Hierarchical Analytical Process is used as a method for establishing a business decision support model. The results highlight a greater contribution to the creation of business value of decisions based on the criterion of benefits and establish a ranking of priorities on IT decisions that lead to the creation of business value.